KEKERASAN BUDAYA PATRIARKHI DALAM KESEHATAN REPRODUKSI DI KECAMATAN KALIKOTES, KLATEN (TINJAUAN DARI PERSPEKTIF GENDER) - Mariyah, Emiliana (PIRAMIDA; Vol. 1, No. 2 Desember 2005)
Management of reproduction health problem is not independent clinically, because pregnancy period need to get attention physically, mentally and also socially. Doctors and medical staffs should include family members at antenatal and gestation periods. Based on the reason, perception and attention of the husband toward the wife along pregnancy and gestation periods is need to be studied. This paper is development of dissertation done in working area of Kalikotes Health Center in Kalikotes Municipality, Klaten, Central Java, which was carried out for one year (1996-1997). Though the research is was done about ten years ago, reproduction health problem which is related with gender still relevant to be discussed nowadays. Out of 161 pregnant women, 47 (44,8 % of them are working mother), to be monitored until they are giving birth. This paper is described through in-depth study related to perception and indifference of the husband toward the wife who pregnant and giving birth. The findings show that both working wife or not working wife have the same physic and mental burdens. Most of pregnant wives do not obtain physical attention from their husband, therefore gender equalisation have not reach by the wife, both who include into public and domestic domains. This reality reflect cultural construction of patriarchy, where women are always accept and do not oppose. This phenomenon is in accordance with the new millennium which there are a shifting from ?domination? theory (feminism practice) to difference and post-feminism.
Keywords: patriarchy culture, reproduction health, gender